The effect of amine-free initiator system and polymerization type on long-term color stability of resin cements: an in-vitro study - İdris Kavut; Mehmet Uğur (BMC, 2022)
Abstract Background This in vitro study evaluated the effect of amine-free initiator system and polymerization type on long-term color change of amine-free light-cure and dual-cure resin cements. Methods Sixty disk-shaped specimens (10 × 1 mm) were prepared from six different amine-free resin cements; NX3 Nexus light-cure (LC) and dual-cure (DC), Variolink Veneer (LC) and Variolink II (DC), Relyx Veneer (LC) and Rely X Ultimate (DC). A feldspathic porcelain specimen (12 × 14 × 0.8 mm) was obtained from a CAD/CAM block (Cerec Blocks; Sirona Dental Systems GmbH, Bensheim, Germany) for color testing. The feldspathic specimen was placed on the resin cement disk and all measurements were performed without cementation. A spectrophotometer was used for color measurements. Specimens were subjected to thermal aging (5 °C and 55 °C; 5000 and 20,000 cycles). Specific color coordinate differences (ΔL, Δa, and Δb) and the total color differences (ΔE00) were calculated after immersion in distilled water for different periods. Normality of data distribution was tested by using the Kolmogorov-Smirnov test. Data were statistically in a model of repeated measures, using multivariate tests and Tukey's multiple comparison tests at a significance level of p < 0.05. Results ∆E00 values of resin cements were influenced by cycle periods, significantly (p < 0.05). The highest ΔE00 values for long term were obtained in the NX3 (DC) (3.49 ± 0.87) and the lowest in the NX3 (LC) (1.41 ± 0.81). NX3 (LC), Variolink (DC), RELY X (LC) resin cements showed clinically acceptable color change after long-term aging (∆E00 < 1.8). Conclusion Light-cure resin cements should be preferred for long-term color stability of full ceramic restorations.